PERAN ORGANISASI INTERNASIONAL REGIONAL DALAM PENYELESAIAN SENGKETA INTERNASIONAL - Anita Anita; Chairul Bariah; Mahmul Siregar (Journal of USU International Law, 2017)
ABSTRACT Dr. Chairul Bariah, S.H., M.Hum* Dr. Mahmul Siregar, S.H., M.Hum** Anita*** Disputes can be happen anywhere and to anyone. Disputes can occur between individual with individual, individual with groups, groups with groups, or countries with other countries. In other words, dispute can be a private, public, national or international problem. Dispute is a situasion where there are parties who feel harmed by another parties, which afterwards the parties expressed his dissatisfaction to the second parties. If both parties shows different opinion, then there is what called a dispute. Disputes between members of the international community can occur due to several reasons, such as for military, political, economic and ideological reasons. A hostile attitude that begins because of dissent can also lead to disputes. It is not imposible when disputes between nations lead to be an armed conflict if both parties do not agree to make peace. As the problem in this research is the role of regional international organizations in international dispute resolution. The research used is normative juridical with descriptive. The data used in this study are primary legal materials, secondary legal materials and tertiary legal materials. Methods of datacollection are using literature study. Data analysis is done qualitatively. The Regional International Organization may serve as a platform for resolving disputes among its members. The role of this organization continues to grow because the international community tends to establishinstitutions in the scope of its territory. Settlement of disputes through regional international organizations also has more value in peaceful dispute settlement in its territory. Keyword: The Regional International Organization, Regional Disputes Resolutions